2020
DOI: 10.1136/annrheumdis-2020-eular.1536
|View full text |Cite
|
Sign up to set email alerts
|

Sat0029 patient-Physician Discordance in Assessment of Disease Activity in Rheumatoid Arthritis

Abstract: Background:In rheumatoid arthritis (RA), global disease activity is commonly assessed, from the patient’s and the physician’s perspective, through a 100mm VAS. Previous studies have commonly shown a considerable discrepancy between the patient’s and physician’s assessment.Objectives:This study aimed evaluating patient-physician discordance in the assessment of disease activity and to explore its determinants.Methods:Cross sectional study including RA patients (ACR/EULAR 2010 classification criteria), aged ≥ 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The correlation between patient and physician assessments was stronger when disease activity was relatively low. This trend is in line with findings from studies on SLE and Rheumatoid Arthritis, indicating that the agreement between patient and physician assessments diminishes at higher disease activity levels [ 3 , 19 , 20 ].…”
Section: Discussionsupporting
confidence: 87%
“…The correlation between patient and physician assessments was stronger when disease activity was relatively low. This trend is in line with findings from studies on SLE and Rheumatoid Arthritis, indicating that the agreement between patient and physician assessments diminishes at higher disease activity levels [ 3 , 19 , 20 ].…”
Section: Discussionsupporting
confidence: 87%
“…These results are comparable to those reported by Harris et al ( 3 ) who found that patient and physician assessments in Systemic lupus erythematosus (SLE) correlated with one another at low but not at high levels of disease activity. Likewise, this effect was shown for Rheumatoid Arthritis ( 12 , 13 ), whereas an opposite trend was observed in the validation of the German Systemic Lupus Activity Questionnaire (SLAQ; for disease activity assessment in SLE ( 14 )).…”
Section: Discussionmentioning
confidence: 94%
“…16 It has also been hypothesised that PGA might be better substituted by the Physician's Global Assessment (PhGA) of disease activity, based on its correlation with objective measures of inflammation, sensitivity to change and ability to correct for common confounders, such as infection and patient-reported outcomes. [17][18][19][20][21][22] Therefore, we aimed to expand our previous study, and to test these newly proposed remission definitions, by assessing their impact on the rate of remission and its association with good radiographic and functional outcomes, the ultimate goals of T2T immunosuppressive therapy.…”
Section: What This Study Addsmentioning
confidence: 99%